Einige inneren Geometrien der Hyperfläche im affinzusammenhängenden Raum - Bliznikas, V. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Близникас. Некоторые внутренние геометрии гиперповерхности пространства аффинной связностиV. Bliznikas. Kai kurios afininio sąryšio erdvės hiperpaviršių vidinės geometrijos